BASIS FOR JUDGES' CONSIDERATIONS IN ISSUE-MAKING REHABILITATION DECISIONS FOR DRUG ADDICTS - Mangiring, Mangiring (UNISSULA Semarang, 2024)
The purpose of this study is to determine the basis for judges' considerations in giving decisions to drug addicts and to determine and analyze the factors that hinder criminal decisions by judges for drug addicts in Batam City. This type of research is normative legal research with a statutory approach with descriptive-prescriptive characteristics that are sourced from secondary data, including: primary legal materials and secondary legal materials. This secondary data includes primary legal materials, secondary legal materials and tertiary materials obtained by means of literature study, then analyzed by legal analysis. Legal provisions regarding sanctions for drug addicts in Law Number 35 of 2009 concerning Narcotics consist of 2 (two) types of sanctions, namely criminal sanctions and action sanctions. Criminal sanctions for drug addicts consist of the death penalty, imprisonment, and fines as stated in the provisions of Article 16, Article 121, and Article 127. Meanwhile, action sanctions are in the form of an obligation to undergo rehabilitation, both medical rehabilitation and social rehabilitation. The provisions regarding rehabilitation for drug addicts are stated in the provisions of Article 54 and Article 103. In addition, the results of this study also explain that the judge's considerations in imposing a criminal sentence on drug addicts in the District Court Decision No. 363/Pid.Sus/2023/PN Btm are based on the provisions of Article 54 and Article 103 of Law Number 35 of 2009 and the Circular of the Supreme Court Number 07 of 2009. The judge's decision in the District Court Decision No. 363/Pid.Sus/2023/PN Btm, in addition to aiming to trap the defendant (drug addict) with criminal sanctions, also aims to cure the defendant (drug addict) from dependence with sanctions in the form of rehabilitation.